ASSESSMENT OF SOIL QUALITY LIMITATIVE FACTORS. A CASE STUDY: SECAŞ, TIMIŞ COUNTY, ROMANIA - Casiana MIHUȚ; Nicoleta MATEOC-SÎRB; Anișoara DUMA COPCEA; Lucian NIȚĂ; Valeria CIOLAC; Adalbert OKROS A.; Daniel POPA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aims, as the main purpose, at assessing the limiting factors of the soil quality in the perimeter of the Commune of Secaş, Timiş County, Romania. To achieve the aim pursued, we identified the main limitative factors of agricultural productivity and soil degradation processes. These were introduced in the database using modern methods, namely the GIS technique, for each soil unit, with “space” representations thereof. The soil surfaces on which each factor and/or degradation process is manifested and which is of particular practical importance in assessing soil quality were calculated automatically. The method used allows one to highlight the soils identified by various maps and cartographic representations. Most of the results were obtained from field work and calculations in the office and laboratory, supplemented by those from O.S.P.A. Timisoara and from literature. The importance of this study materialized in a complex database comprising all soil units in the studied perimeter, limiting factors specific to this area and degradation processes, as well as the establishment of fertility classes, i.e., the quality of existing soils in the studied area. The study highlights that the soils of the Commune of Secaş falls into grade III and IV fertility (quality).